2017
DOI: 10.24251/hicss.2017.574
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Business-IT Alignment - Digital Business Strategies as a Paradigmatic Shift: A Review and Research Agenda

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 62 publications
(137 reference statements)
0
48
0
Order By: Relevance
“…As long ago as 2002, Lin and Sun were suggesting that 'When an IT system is viewed as a part of the business organisation, and both the IT and business systems are designed in the same time, the gap between them can be minimised ' (2002, p.251). In the context of smart work systems, the idea is now receiving recognition that dynamic co-evolution of socio-technical elements is needed (Kahle et al 2017;Amarilli et al 2017). A contemporary socio-technical approach is therefore required to support an on-going journey towards smarter working and living.…”
Section: Moving To Industry 50mentioning
confidence: 99%
“…As long ago as 2002, Lin and Sun were suggesting that 'When an IT system is viewed as a part of the business organisation, and both the IT and business systems are designed in the same time, the gap between them can be minimised ' (2002, p.251). In the context of smart work systems, the idea is now receiving recognition that dynamic co-evolution of socio-technical elements is needed (Kahle et al 2017;Amarilli et al 2017). A contemporary socio-technical approach is therefore required to support an on-going journey towards smarter working and living.…”
Section: Moving To Industry 50mentioning
confidence: 99%
“…Extant research provides substantial insights into the disruption of markets through radical digital innovations and on the input and output of DT processes [5,27]. However, there is a scarcity of longitudinal studies [10,33] investigating the underlying remolding of resource combinations and organizational capabilities in DT [19,20]. We contribute in two regards by offering a detailed and microlevel analysis of how the DT process can unfold in practice [33].…”
Section: Discussionmentioning
confidence: 99%
“…A relative amount of literature draws on DC theory to explore constitutive elements of DT. However, research on DC building in relation to DT remains scarce [19,33], with some noticeable exceptions. First, Li et al, [20] demonstrated that successful DT initiatives by entrepreneurs in SME's entail far more than just embracing digital technology.…”
Section: Dynamic Capabilities In Digital Transformationmentioning
confidence: 99%
“…It is suggested, there-fore, that a concept of alignment between separate organizational sub-systems is not a useful construct. The idea is now receiving recognition that dynamic co-evolution of socio-technical elements is more relevant [33] [34]. A contemporary socio-technical approach is therefore required to support an on-going journey towards excellence.…”
Section: Dynamic Open Systems Approachmentioning
confidence: 99%